Analysis of SARS-CoV-2 mutations in the United States suggests presence of four substrains and novel variants - Rui Wang (Nature Portfolio, 2021)
Rui Wang et al. report a comprehensive analysis of nearly 13,000 SARS-CoV-2 genome sequences isolated from patients in the United States, comprising more than 7000 single mutations. They show that SARS-CoV-2 genomes cluster into four distinct groups and that two of these groups are potentially more infectious, underlining the urgent need for viral control strategies in the US.